The Impact of Innovation-Driven Digital Transformation on Export Performance of SMEs - Tran, The Tuan; Tran, Khanh; Tho, Do Thi (Ital Publication, 2025)
This study uses quantitative research methods to analyze the impact of innovation-driven digital transformation on the export performance of small and medium-sized enterprises in Vietnam. Data was collected from 403 valid responses from exporting enterprises and analyzed using the partial least squares structural equation model (PLS-SEM). The factors considered include management capacity, corporate culture, competitive pressure, enterprise resources, and government support. Digital transformation was identified as an intermediary variable between these factors and export performance. The research results indicate that digital transformation directly and significantly impacts export performance (β = 0.523, p < 0.01). At the same time, management capacity (β = 0.296, p < 0.01) and competitive pressure (β = 0.295, p <0.01) are important factors promoting the digital transformation process, while enterprise resources (β = 0.274, p < 0.01) and enterprise culture (β = 0.145, p < 0.01) also positively support it. Despite having a lower impact, government support (β = 0.118, p < 0.01) still encourages enterprises to apply digital technology. The study provides practical insights for policymakers and businesses to optimize digital transformation strategies, emphasizing the need for more substantial managerial capabilities and competitive adaptability. Unlike previous research, this study highlights corporate culture and competitive pressure as crucial factors shaping digital transformation in Vietnam’s export sector. Based on the results, the study proposes solutions to enhance competitiveness and export efficiency for small and medium-sized enterprises in Vietnam.